APPLICATION OF COPPER OXIDE PAINTS AS PREVENTION FOR MACROFOULING ATTACHMENT ON A MARINE FLOATING NET CAGE - Sri Rejeki; Titi Susilowati; Restiana Wisnu Aryati (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Macrofouling is one of the major problems on a marine net cage culture. The attachment of macrofouling could cover the net cage and thus reduce the water circulation in the cage. Application of copper oxide paints may be able to solve that problem. A field experiment with Completely Randomizes Design was applied with 9 treatments: paint without biocide; paints contained: 5% Copper Oxide; 10% Copper Oxide; 1% Chlorothalonil; 1% Chlorothaloni + 5% Copper Oxide; 1% Chlorothaloni + 10% Copper Oxide; 1% Zinc Omadine; 1% Zinc Omadine + 5% Copper Oxide; 1% Zinc Omadine + 10% Copper Oxide, each treatment was replicated 3 times. The research was done on July – September 2007 at Hanura Bay Lampung. Data of the abundance and diversity of macrofouling were collected weekly. The results showed that the application of copper oxide paints affected the macrofouling attachment significantly (P < 0, 01). The best result was antifouling paints contained Copper Oxide, and combination between Copper Oxide with Chlorothalonil and Zink Omadine. However, from the economical point of view, paint with 5% Copper Oxide could be suggested for preventing macrofouling attachment on the marine net cage.